Analysing the Impact of MPI-2 Dynamic Process Creation to the Game of Life Problem - Lorenzon, Arthur Francisco; Cera, Márcia Cristina; Rossi, Fábio Diniz (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2012: Anais do XIII Simpósio em Sistemas Computacionais de Alto Desempenho, 2012)
MPI-2 dynamic process creation brings new opportunities, since it allows to add some flexibility into MPI applications. However, the spawning of processes is synchronous and it establishes an hierarchical communication relationship among processes. This paper investigate the impact of MPI-2 features over the Game of Life problem. We implement different versions of our test application aiming to identify both, spawning and hierarchical communication overhead. Our results show the impact achieved with our test environment. In addition, we discuss some directions to reduce the overhead taking advantage of MPI features.